Fabrication of supramolecular cyclodextrin–fullerene nonwovens by electrospinning - Yoshida, Hiroaki; Kikuta, Ken; Kida, Toshiyuki (Beilstein Journal of Organic Chemistry, 2019)
Direct electrospinning of small molecules has great potential to fabricate a new class of fiber materials because this approach realizes the creation of various functional materials through the numerous molecular combinations. In this paper, we demonstrate a proof-of-concept to fabricate supramolecular fiber materials composed of cyclodextrin (CD)–fullerene inclusion complexes by electrospinning. Similar to the molecular state of fullerenes in solution, the resulting fibers include molecularly-dispersed fullerenes. We believe such a concept could be expanded to diverse host–guest complexes, opening up supramolecular solid materials science and engineering.
Keywords: cyclodextrin; electrospinning; fullerene; nanofiber; supramolecular complex

(untitled) - O'Brien, J. P.; Fahnestock, S. R.; Termonia, Y.; Gardner, K. H. (Adv. Mater., 1998)

(untitled) - Fratzl, P.; Weinkamer, R. (Prog. Mater. Sci., 2007)

(untitled) - Greiner, A.; Wendorff, J. H. (Angew. Chem., Int. Ed., 2007)

(untitled) - Shenoy, S. L.; Bates, W. D.; Frisch, H. L.; Wnek, G. E. (Polymer, 2005)

(untitled) - Gupta, P.; Elkins, C.; Long, T. E.; Wilkes, G. L. (Polymer, 2005)

(untitled) - McKee, M. G.; Layman, J. M.; Cashion, M. P.; Long, T. E. (Science, 2006)

(untitled) - Cashion, M. P.; Li, X.; Geng, Y.; Hunley, M. T.; Long, T. E. (Langmuir, 2010)

(untitled) - Singh, G.; Bittner, A. M.; Loscher, S.; Malinowski, N.; Kern, K. (Adv. Mater., 2008)

(untitled) - Celebioglu, A.; Uyar, T. (Chem. Commun., 2010)

(untitled) - Celebioglu, A.; Uyar, T. (RSC Adv., 2013)

(untitled) - Kida, T.; Sato, S.-i.; Yoshida, H.; Teragaki, A.; Akashi, M. (Chem. Commun., 2014)

(untitled) - Costoya, A.; Concheiro, A.; Alvarez-Lorenzo, C. (Molecules, 2017)

(untitled) - Yan, X.; Zhou, M.; Chen, J.; Chi, X.; Dong, S.; Zhang, M.; Ding, X.; Yu, Y.; Shao, S.; Huang, F. (Chem. Commun., 2011)

(untitled) - Tayi, A. S.; Pashuck, E. T.; Newcomb, C. J.; McClendon, M. T.; Stupp, S. I. (Biomacromolecules, 2014)

(untitled) - Palarz, S.; Smarsly, B.; Bronstein, L.; Antonietti, M. (Angew. Chem., Int. Ed., 2001)

(untitled) - Celebioglu, A.; Uyar, T. (Langmuir, 2011)

(untitled) - Chen, M.; Nielsen, S. R.; Uyar, T.; Zhang, S.; Zafar, A.; Dong, M.; Besenbacher, F. (J. Mater. Chem. C, 2013)

(untitled) - Kroto, H. W.; Heath, J. R.; O'Brien, S. C.; Curl, R. F.; Smalley, R. E. (Nature, 1985)

(untitled) - Ruoff, R. S.; Tse, D. S.; Malhotra, R.; Lorents, D. C. (J. Phys. Chem., 1993)

(untitled) - Prato, M. (J. Mater. Chem., 1997)

(untitled) - Andersson, T.; Nilsson, K.; Sundahl, M.; Westman, G.; Wennerström, O. (J. Chem. Soc., Chem. Commun., 1992)

(untitled) - Yoshida, Z.-i.; Takekuma, H.; Takekuma, S.-i.; Matsubara, Y. (Angew. Chem., Int. Ed. Engl., 1994)

(untitled) - Takekuma, S.-i.; Takekuma, H.; Matsumoto, T.; Yoshida, Z.-i. (Tetrahedron Lett., 2000)

(untitled) - Nishimura, T.; Nakajima, M.; Maeda, Y.; Uemura, S.; Takekuma, S.-i.; Takekuma, H.; Yoshida, Z.-i. (Bull. Chem. Soc. Jpn., 2004)

(untitled) - Nishibayashi, Y.; Saito, M.; Uemura, S.; Takekuma, S.-i.; Takekuma, H.; Yoshida, Z.-i. (Nature, 2004)

(untitled) - Braun, T.; Buvári-Barcza, Á; Barcza, L.; Konkoly-Thege, I.; Fodor, M.; Migali, B. (Solid State Ionics, 1994)

(untitled) - Komatsu, K.; Fujiwara, K.; Murata, Y.; Braun, T. (J. Chem. Soc., Perkin Trans. 1, 1999)

(untitled) - Rusa, C. C.; Bullions, T. A.; Fox, J.; Porbeni, F. E.; Wang, X.; Tonelli, A. E. (Langmuir, 2002)

(untitled) - Marui, Y.; Kida, T.; Akashi, M. (Chem. Mater., 2010)

(untitled) - Kim, D.; Lee, M.; Suh, Y. D.; Kim, S. K. (J. Am. Chem. Soc., 1992)

(untitled) - Liu, W.; Wei, J.; Chen, Y.; Huo, P.; Wei, Y. (ACS Appl. Mater. Interfaces, 2013)

(untitled) - Murthy, C. N.; Geckler, K. E. (Chem. Commun., 2001)

(untitled) - Andersson, T.; Sundahl, M.; Westman, G.; Wennerström, O. (Tetrahedron Lett., 1994)

(untitled) - Lee, J.; Tae, G.; Kim, Y. H.; Park, I. S.; Kim, S.-H.; Kim, S. H. (Biomaterials, 2008)